Contesting adaptation synergies: political realities in reconciling climate change adaptation with urban development in Johannesburg, South Africa - Hetz Karen (Spring-Verlag Berlin Heidelberg, 2016)
Strategies to promote synergistic responses to both urban development issues and climate change adaptation have become central to policy advice on adaptation. However, the empirical evidence for the effective utilisation of adaptation synergies in planning practices is insufficient. Taking urban planning in Johannesburg as a case study and using the risks of flooding as an illustrative example, this qualitative study explores how adaptation synergies can be realised in planning practices. In this specific case, significant synergy possibilities in planning practices are not observed. Instead, political challenges of reconciling adaptation measures with planning responses to the considerable developmental challenges of urban divide and multiple urban risks in Johannesburg substantially limit the response space for adaptation practices, including those achievable through synergies. Insights gained in this study underline the necessity of giving greater attention to the empirics of observed synergies. The study provides initial indications that it may be necessary to adjust elements of the conceptual arguments concerning adaptation synergies and related policy advice.
Keywords: Urban planning || Adaptation practice || Adaptation barriers || Multiple risks || Global South ||